2020
DOI: 10.3126/jnps.v40i3.30008
|View full text |Cite
|
Sign up to set email alerts
|

Teething Beliefs, Misconceptions, and Practices Among Mothers Attending a Tertiary Hospital in Nigeria: Implications for Child Health and Clinical Practice

Abstract: Introduction: Teething is a physiologic process that begins during infancy. However, some mothers often attribute certain symptoms to teething. In this study, we assessed the opinions and practices of mothers attending a tertiary health facility in Nigeria on teething. Methods: This was a cross-sectional, descriptive study conducted among caregivers of children presenting to the out-patient department of a tertiary hospital, Southwestern Nigeria. Results: Five hundred and sixteen mothers were studi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
2
3
0
Order By: Relevance
“…In a similar study, vitamins accounted for 37% of medicines used among Finnish children below age 12 (Ylinen et al, 2010). The use of vitamin C among Nigerian infants can be said to be high as our study portrayed and this is also supported by a previous study among another pediatric population in Nigeria (Oshikoya et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…In a similar study, vitamins accounted for 37% of medicines used among Finnish children below age 12 (Ylinen et al, 2010). The use of vitamin C among Nigerian infants can be said to be high as our study portrayed and this is also supported by a previous study among another pediatric population in Nigeria (Oshikoya et al, 2007).…”
Section: Discussionsupporting
confidence: 86%
“…Antibacterials were used to a substantial proportion in this population with ampicillin /cloxacillin being the most frequently used; this trend corroborates another study in Nigeria where ampicillin/cloxacillin accounted for the most frequently used antibacterial and it was mostly not prescribed by the physician (Oshikoya et al, 2007). However, a recent study by Ahwinahwi et al (2021) reported that antibacterials were frequently prescribed for young children attending an outpatient clinic for young children.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…More culturally centred remedies include amber teething necklaces, gum incision [ 16 ], applying herbs to the gums, and the use of rehydration salts and vitamins amongst many others. Quaternary prevention (the avoidance of over medicalisation and treatments that might have more harm than benefit) [ 2 , 17 ] should be a constant in guiding treatment recommendations. Some teething treatments involve medicaments (such as topical anaesthesia), are unproven and might be unnecessary [ 18 ], the active components and potential adverse effects of some are unknown, and others have caused significant harm [ 19 ].…”
Section: Introductionmentioning
confidence: 99%